Позиціонування вугільної галузі у зовнішньому енергетичному балансі України - Гришко, І.Л. (Економіка промисловості, 2012)
Здійснено формування зовнішнього енергетичного балансу з розрахунком показника чистого експорту. Виконано комплексну оцінку співвідношення обсягів виробництва та споживання вугілля в Україні. Виявлено невідповідність обсягів виробленого та спожитого вугілля та його акумуляцію в Україні. Обґрунтовано необхідність зменшення обсягів імпорту вугілля.
Ключові слова: виробництво, зовнішній баланс, імпорт, комплексна оцінка, споживання, формування, чистий експорт. Осуществлено формирование внешнего энергетического баланса с расчетом показателя чистого экспорта. Выполнена комплексная оценка соотношения объемов производства и потребления угля в Украине. Выявлены несоответствие объемов произведенного и потребленного угля и его аккумуляция в Украине. Обоснована необходимость уменьшения объемов импорта угля.
Ключевые слова: внешний баланс, импорт, комплексная оценка, потребление, производство, формирование, чистый экспорт. Under present-day conditions it is important to maximize the consumption of energy resources produced in Ukraine, in particular coal resources. It will contribute to solving several macroeconomic problems of Ukraine like raising the energy assurance level as a component of national security of Ukraine, improving the competitiveness of domestic enterprises and the trade balance of Ukraine.
At the present stage of development the most popular energy resources are oil and natural gas which is conditioned by their high heating and ecological characteristics. At the same time the reduction of these resources, irregularity of their deposits and other objective factors make for consumption of local energy resources, in particular coal resources. It is defined that foreign energy balance is an index system that shows the demand-consumption ratio of an energy resource in a given period of time inside the country.
A foreign energy balance model has been designed which includes calculation of the net export and makes it possible to clear up the modern tendencies that established in our country’s external economic relations of energy resources trade. It has been proved that the basic factor reducing the net export of energy resources is a great volume of imported natural gas though the trade balance of coal and peat operations is negative as well. A complex evaluation of production and consumption ratio of coal in Ukraine based on reduction coefficient to oil equivalent has been carried out which makes it possible to reveal the discrepancy between the volume of coal produced and the volume of coal consumed with its latter accumulation in Ukraine. The necessity of reducing the volume of coal import is proved.
Keywords: foreign energy balance, import, complex evaluation, consumption, production, formation, net export.